Tiebout with Politics: Capital Tax Competition and Constitutional Choices - Perroni, C.; Scharf, K. A. (Review of Economic Studies, 2001)
This paper examines how capital tax competition affects jurisdiction formation. We describe a non-cooperative locational model of public goods provision choices, where the levels of taxation and the local public good varieties provided within jurisdictions are selected by majority voting, and where equilibrium jurisdictions consist of consumers with similar tastes. We show that interjurisdictional tax competition results in an enlargement of jurisdictional boundaries, and, even in the absence of intrajurisdictional transfers, can raise welfare for all members of a jurisdiction.